Land-use homogenization reduces the occurrence and diversity of frugivorous birds in a tropical biodiversity hotspot - Bonfim, Fernando César Gonçalves; Galetti, Mauro [UNESP]; Benchimol, Maíra; Morante-Filho, José Carlos; Magioli, Marcelo; Cazetta, Eliana (Wiley, 2024)
Understanding how human-modified landscapes maintain biodiversity and provide ecosystem services is crucial for establishing conservation practices. Given that responses to land-use are species-specific, it is crucial to understand how land-use changes may shape patterns of species diversity and persistence in human-modified landscapes. Here, we used a comprehensive data set on bird distribution from the Brazilian Atlantic Forest to understand how species richness and individual occurrences of frugivorous bird species responded to land-use spatial predictors and, subsequently, assess how ecological traits and phylogeny modulated these responses. Using Bayesian hierarchical modeling, we reveal that the richness of frugivorous birds was positively associated with the amount of native forest and negatively with both agriculture and pasture amount at the landscape scale. Conversely, the effect of these predictors on species occurrence and ecological traits was highly variable and presented a weak phylogenetic signal. Furthermore, land-use homogenization (i.e., the conversion of forest to pasture or agriculture) led to pervasive consequences for forest-dependent bird species, whereas several generalist species thrived in deforested areas, replacing those sensitive to habitat disturbances.
Keywords: Brazil; deforestation; ecological traits; frugivory; habitat loss; species occurrence